Correction: Overexpression of MyrAkt1 in Endothelial Cells Leads to Erythropoietin- and BMP4-Independent Splenic Erythropoiesis in Mice. - Rebekah K O'Donnell; Whitney E Goldstein; Carole Perruzzi; Laura E Benjamin; William C Aird (PLoS ONE, 2013)
[This corrects the article on p. e55095 in vol. 8.].